Percurso gramatical brasileiro: estudo descritivo-analítico de gramáticas produzidas por acadêmicos – contribuição à história da gramática no Brasil - Silva, Alexandre José da (2020)
This thesis, divided in four chapters, and situated in the line of research mode of The Linguistic Ideas History (HIL), describes and analyses linguistic instruments – Grammar - produced by University Professors, denominated Academics. We start from the defense that the promulgation of NGB (1959) contributed for a new moment of massive grammatization, or as such, for a neogrammatization. In result of this, the grammars post-NGB produced by academics represent the continuum/discontinuum movement in reference to grammatical studies. As such, we have the following problematic: the publication of grammar works produced by university professors (academics) from courses of Languages/Linguistics shows an synonym of continuity (tradition, conservation, statism), and/or discontinuity (dynamism, creative capacity, innovation) in grammar. For such, the following propositions, that deal with different aspects of the problem, were observed and put into investigation: the works, even beeing very different in between themselves, keep similarities with regard to presentation, description and interpretation of grammatical categories; is from the so-called traditional theory that come the concepts on the basis of which new explanations for ancient phenomena are reformulated; the works present relative stability in deference to formal composition and content; the works, often are revised, adapted (facilitated, commented) and restructured for pocket editions; the publications present terminological indefiniteness, since is hard to measure if they configure grammar treaties or linguistic treaties (gramtinguísticas). It is worth mentioning that the following objectives were considered: weighing of the produced “academic” grammars since promulgation of the NGB (Brazilian Grammar Nomenclature); reading and analyses of the grammar introductions aiming to observe the author’s grammar discourse; description and analyses and of the works, by having as investigative scope two great grammar subjecs: Adverb (metaterm that designates a class belonging to the study of Morphology) and Sentence (metaterm that designates an studied structure in the field of Syntax); proposal of typology ordering for grammars. So we conclude, that the continuum/discontinuum of the grammar discourse elaborated by the authors allowed the realization of a typology that confirms the fact that the works transiting by Tradition, Tradition-Innovation and Innovation-Gramatinguísticas